The Role of the Human Papillomavirus (HPV) in Cervical Cancer: A Review about HPV-Induced Carcinogenesis and Its Epidemiology, Diagnosis, Management and Prevention - Karl Bonello; Renald Blundell (University Library System, University of Pittsburgh, 2016)
The human papillomavirus (HPV) was the first virus known to induce carcinogenesis and is associated with cancers of the uterine cervix, anogenital tumors and malignancies of the head and neck. This paper reviews the structure and basic genomic characteristics of the virus and outlines the clinical involvement of the main HPV serotypes, focusing on the carcinogenic role of HPV-16 and 18. The mechanisms that occur in the development of cervical neoplasia due to the oncogenic proteins E6 and E7 which interfere with the regulation of the cell cycle through their interaction with p53 and retinoblastoma protein are described. Epidemiological factors, diagnostic tools and the management of the disease are also reviewed, along with the available vaccines to prevent the viral infection. Insights on current research on involvement of oxidative stress and micro-RNAs in cervical carcinogenesis are also explored as they may unlock new means of diagnosis and treatment in the future.